Juggling to stay afloat: Debt and health under financialization - Annie Harper; Tommaso Bardelli; Katherine Kwok (Elsevier, 2024)
Household debt has dramatically increased in the United States in the past four decades, notwithstanding a temporary reprieve during the Covid-19 Pandemic. While debt has expanded across social groups, low-income individuals are most negatively impacted, taking on high-cost debt that they struggle to repay, often simply to meet basic needs. This article explores indebtedness among low- and moderate-income US households, and its association with physical and mental health. While most existing studies explore health effects of specific debt types, or monetary value of total debt, our research proposes a categorization of debt into three types (potential wealth-building, problem short-term, and non-loan debt) that is more meaningful in health research and addresses the experience of managing multiple and intersecting debts, common among low-income households. Using mixed methods, we show how these debts are experienced by debtors, resulting in them feeling overwhelmed, anxious, and stressed, ultimately taking a toll on both their physical and mental health.